Effects of game location, quality of opposition and players` suspensions on performance in elite male handball - Debanne, T. (Revista Internacional de Ciencias del Deporte, 2018)
Based on the territoriality concept, the aim of this study was to investigate the influence of game location, quality of opposition, and players` exclusions on team performance (score differential). The sample consisted of 364 games (182 during each regular season 2014-2015 and 2015-16) from the French male professional league (LNH). In contrast to the territoriality theory, the results did not show that home teams were more sanctioned than visiting teams. Furthermore, using Analysis of Variance, the findings highlighted the fact that the quality of the opponent overcomes the home advantage effect and the existence of an interaction effect of [game location] x [quality of opposition] x [players`exclusions difference] on the score differential. Indeed, home teams with strong opposition perform better when they are more sanctioned (M = -2.26; SD = 3.53) than when they are less sanctioned (M = -4.9; SD = 4.69). Concerning visiting teams, faced with strong opposition, they perform better when they are less sanctioned (M = -2.8; SD = 4.5) than when they are more sanctioned (M = -5.4; SD =3.5) or when players` exclusions are balanced (M = -5.7; SD = 5.4); also, faced with balanced opposition they perform better when they are more sanctioned (M = 0.03; SD = 4.85) than when players` exclusions are balanced (M = -2.1; SD = 4.34). These results can contribute to a better understanding of the situational determining factors of elite handball performance, helping coaches to prepare their own team accordingly.